THE PHYSICAL STABILITY OF COCONUT MILK EMULSION - Hamad, Alwani (Techno Jurnal Ilmu Teknik, 2011)
Coconut milk, a term for the aqueous extract from coconut solid meat, is often uses in Asian cuisines as well as other part of the world. Studies to investigate the stability of the coconut milk emulsion often report inconsistently. The information about the stability of the coconut milk emulsion literature is used to keeping quality of coconut milks extract in processing and preservation (particularly by canning, spray-drying and freezing) and new food uses coconut milk.Â Key word : Coconut milk, Stability emulsion, droplet size, coconutÂ